History of the Javanese Calendar in the Era of Aji Saka and Sultan Agung - M. Saifulloh; Ahmad Izzuddin; Eman Sulaiman (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2026)
A calendar is a system that provides daily, monthly, and yearly time by following natural phenomena, namely the apparent movement of the sun from east to west. Calendars did not simply appear; they were influenced by social culture and history. The Javanese calendar system was created by Aji Saka and later modified by Sultan Agung. An interesting aspect of both systems is that they follow Java's cultural traditions. The system used at the beginning of the Javanese calendar was the solar calendar system. However, with the introduction of new cultures and religions to Java, namely Islam and its influence, the calendar changed but continued to follow Aji Saka's annual numbers. The only changes in Sultan Agung's calendar system were the names of the months and the shift from a solar to a lunar calendar. This change followed the Islamic calendar, which had already been influenced by the arrival of Islam from India and Arabia. The number of days in a year also changed from 365 to 355 days. This research method uses qualitative literature that focuses on the historical origins, compares the two systems, and then examines their advantages and disadvantages.